Lawrence Head Volcanics and Dunnage Mélange, Newfoundland Appalachians: Origin by Ordovician Ridge Subduction or in Back-Arc Rift? - Schoonmaker, Adam; Kidd, William S.F.; DeLong, Stephen E.; Bender, John F. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
This paper reviews the geological setting and reports new geochemical trace element data from the Ordovician Lawrence Head Volcanics (LHV) and the underlying gabbro sills in the Exploits Group. In combination with existing published analyses and ages of these rocks, the volcanic rocks and sills are indistinguishable in composition and age, and the data are consistent with the hypothesis that they represent the same (mostly E-MORB composition) magmatic event in the early–mid Darriwilian (~465 ± 2 Ma). The LHV and their enclosing strata show regional evidence for: 1) upward decline of volume and grain size of arc-derived volcaniclastic materials over the uppermost interval of turbidite sedimentary strata below the LHV; 2) change to shallow marine conditions locally by the end of the LHV event, followed immediately by significant subsidence, and 3) no evidence of coarse-grained clastic input, nor of normal faulting, during or immediately after LHV magmatism. Ridge–trench interaction (ridge subduction) at a subduction system is consistent with all of these features and spatial distribution of related elements, but a rift (back-arc) origin over a subduction zone can only accommodate the compositions, and is inconsistent with the geological evidence. The Dunnage Mélange (DM) has been interpreted either as olistostromal in a developing back-arc rift basin, or as a subduction accretionary prism. Peraluminous intrusions in the mélange (Coaker Porphyry ― CP) are more readily explained by ridge subduction, and a previously reported zircon age (469 ± 4 Ma) is consistent with the age of the LHV and gabbro sills, also interpreted as products of ridge subduction. Localization of the CP in the eastern area of DM, and of most of the large LHV-derived volcanic blocks in the western DM, suggests a slightly younger age, and perhaps a different mechanism, for the origin of the western DM.